IMPLEMENTASI PERATURAN MENTERI PERDAGANGAN NOMOR 46 TAHUN 2009 TENTANG PENERBITAN SURAT IZIN USAHA PERDAGANGAN DI KANTOR PENANAMAN MODAL DAN PELAYANAN PERIZINAN KABUPATEN SANGGAU - Alip Samudera Mahesa E.01109089 (FISIP Universitas Tanjungpura, 2013)
Nowdays,there are so many entreupreneurs who haven’t make illegal permissions of their own business, and the duration of bussiness lisence, they had become the problem in sanggau regency and with this scription, writter try to describe about implementation regulation minister of commerce number 46 year 2009 about legality bussiness lisence of commerce. This scription also intended to improve lisencimg service proses to produce bussiness lisence legally at investment and lisencing service office get better. In this research, writter use descritive qualitative research method. Service lisencing proses in investment and lisencing service office of sanggau regency, had a 3 factors, they are organization, interpretation, and aplication to implementation regulation Minister of Commerce number 46 year 2009 about legality bussiness lisence of commerce. Based on the three factors, writter conclude the factors that hamper the implementation regulation process, there are human resources deficiency and not yet realized one stop service programe in investment and lisencing srvice office of Sanggau regency. In this part, writter want to suggets the Goverment to immmediately realize one stop service programe and pay attention to human resources deficiency in Investment and Lisencing Service programe of Sanggau Regency.Keyword : Lisencing Service, Bussiness Lisence Of Commerce, Organization, Interretation, Aplication